2020
DOI: 10.4028/www.scientific.net/jbbbe.45.49
|View full text |Cite
|
Sign up to set email alerts
|

The Characterization of Bovine Bone-Derived Hydroxyapatite Isolated Using Novel Non-Hazardous Method

Abstract: Bovine bone is a considerable source for the production of hydroxyapatite. The recent study reported a novel method to extract hydroxyapatite from bovine bone without producing hazardous residue. The bovine bones were cut and boiled in the opened chamber followed by boiling in pressurized tank. The bones were then soaked into 95% ethanol. Calcination was then conducted in 800°C, 900°C and 1,000°C, for 2 hours. The result was then grinded and sieved. The powder then was characterized using Fourier transform inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
27
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(31 citation statements)
references
References 11 publications
3
27
1
Order By: Relevance
“…is is possibly because BHA-GEL as the main material for the matrix resembles the inorganic and organic components of bone. Because of this, the implants may also function as bone tissue scaffold and make the growth of blood vessels in the damaged tissue faster than the negative control group [4,11,12].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…is is possibly because BHA-GEL as the main material for the matrix resembles the inorganic and organic components of bone. Because of this, the implants may also function as bone tissue scaffold and make the growth of blood vessels in the damaged tissue faster than the negative control group [4,11,12].…”
Section: Discussionmentioning
confidence: 99%
“…Bovine hydroxyapatite (BHA) was extracted from bovine bone at temperature of 1000°C based on the procedure of the previous study [4]. A total of 10 grams of BHA, 5 ml 20 wt% gelatin (GEL, Cartino, ailand), and 10% gentamicin (GEN, Yantai Justaware Pharmaceutical, China) are mixed until reaching homogeneous mixture to form a mass that can be made as granule.…”
Section: Fabrication Of Bha-gel-gen Implantmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydroxyapatite (HA) is a biomaterial used for the production of orthopedic and dental implants. Typically, HA is used as a single material or composite in combination with other materials [1][2][3], a coating agent for bone graft [1,4,5], and a matrix for drug delivery systems targeting bone tissue [6]. HA is widely used because it contains similar physical and chemical components to those of natural HA present in bone tissue [2].…”
Section: Introductionmentioning
confidence: 99%
“…Typically, HA is used as a single material or composite in combination with other materials [1][2][3], a coating agent for bone graft [1,4,5], and a matrix for drug delivery systems targeting bone tissue [6]. HA is widely used because it contains similar physical and chemical components to those of natural HA present in bone tissue [2]. Moreover, studies reported that HA induced a favorable immune response [7], exerted an angiogenic effect on defective bone tissue [8,9], and activated osteoblasts and osteoclasts for bone tissue remodeling by accelerating the differentiation of these cells [10,11].…”
Section: Introductionmentioning
confidence: 99%